Innovation Activities and Financial Performance: The Case of Kosovo (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2018)
The aim of this research is to investigate the impact of innovation activities and its determinants on firm performance. For the empirical analysis of the study we use Business Environment Enterprise Performance Surveys (BEEPS) firm-level data conducted by the World Bank and the European Bank for Reconstruction and Development (EBRD) in 2013-2014. To examine the relationship between innovation activities and its determinants to firm performance we applied multiple regression analysis and descriptive statistics on 202 companies from Kosovo. Moreover, empirical evidence results of neighbouring countries were compared to our findings for each determinant and its effect on firm performance. By investigating the innovation-performance relationship we found sufficient evidence that supports the main hypothesis. As for the innovation determinants our results indicate that factors as domestic ownership, age, and training affect the tendency of firms to innovate, thus positively affecting firm performance.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.